(untitled) (Research, Society and Development, 2025)
Soil plays an essential role for life and food production, but it is facing increasing degradation, compromising its ecological and productive functions. Aggregate stability is a fundamental indicator of the soil’s structural quality, directly reflecting its capacity to support crops and environmental services. The aim of this study was to assess soil aggregation in different horizons of a profile located in the municipality of Santo Antônio do Leverger, in the state of Mato Grosso. Textural characteristics and aggregate stability were analyzed using the parameters of weighted mean diameter, geometric mean diameter and aggregate stability index. The samples were taken from six horizons defined in an open trench in Yellow Latosol, with thirty deformed samples used for laboratory analysis. Texture was determined using the pipette method, while aggregate stability was assessed using wet sieving. The results indicated that aggregate stability varied between the horizons, being higher in the surface horizon. Multivariate statistical analysis confirmed a significant effect of depth on soil structural stability. The joint assessment of the parameters proved essential for a precise understanding of structural quality, pointing to the importance of considering the complete soil profile for sustainable management and the formulation of more effective agronomic policies.